(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper explores need, development and main features operational subsystem of FOIS for IR which is called Rake Management system. It is a system for management and control of freight movement that also assists managers to optimize asset utilization. It has main advantage of providing real time data for wagons/ rake for proper decision making. The paper also explores advantages and certain shortcomings in the interface mechanisms and future integration with latest technologies